2021
DOI: 10.25105/ber.v21i1.9280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Supervisor Support and Rewards and Recognition Toward Performance Through Work Satisfaction and Employee Engagement in Employee Marketing Banks

Abstract: <p><em>The company as an organization has a dependency on individuals within the company itself. Employees as individuals in the company are part of the organizational structure that has a major role in determining the achievement of company goals. In the perspective of employees, direct supervisors' attitudes and actions can increase employee engagement or even create an atmosphere where an employee becomes disengaged (feeling not part of the company/organization). In addition to marketing employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Perceived supervisor support is also an employee's assessment of the contribution and welfare provided by supervisors to the organization as a task in developing the organization [22]. Employees perceive supervisors as supervisors in the organization whose role is maximized for employees, including providing support [23]. Employees perceive supervisors as supervisors in the organization whose role is maximized for employees including providing support [15].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Perceived supervisor support is also an employee's assessment of the contribution and welfare provided by supervisors to the organization as a task in developing the organization [22]. Employees perceive supervisors as supervisors in the organization whose role is maximized for employees, including providing support [23]. Employees perceive supervisors as supervisors in the organization whose role is maximized for employees including providing support [15].…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Perceived leader's support is defined as employees' perception or belief of how their leaders value and appreciate their well-being as well as their contribution towards the organisations (Karasek, 1985). Leader's support has been reported by many (i.e., Akinlawon & Jamila, 2022;Kenny et al, 2020;Kurniawan & Anindita, 2021), to be influential towards employee engagement. Nevertheless, the researchers have identified that most previous studies studied the relationship between a leader's support and engagement that involved employees from setting other than the healthcare industry (i.e., banking industry, higher educational industry, and manufacturing industry).…”
Section: Literature Reviewmentioning
confidence: 99%